Zyxin Mediates Vascular Repair via Endothelial Migration Promoted by Forskolin in Mice - Kang, Xuya; Deng, Yanan; Cao, Yang; Huo, Yingqing; Luo, Jincai (Frontiers in Physiology, 2021)
Background and Purpose: Endothelial repair upon vascular injury is critical to protecting vessel integrity and preventing the development of vascular disorders, but the underlying mechanisms remain poorly understood. Here, we investigated the role of zyxin and its associated cAMP signaling in the regulation of re-endothelialization after vascular injury. Experimental Approach: In zyxin-/- and wild-type mice, wire injury of the carotid artery was carried out, followed by Evans blue staining to evaluate the re-endothelialization. Mice with endothelium-specific zyxin knockout were used to further determine its role. An in vitro wound-healing assay was performed in primary human endothelial cells (ECs) expressing zyxin-specific short-hairpin RNAs (shRNAs) or scrambled controls, by measuring cell migration and proliferation. The effects of the cAMP signaling agonist forskolin were assessed. Key Results: The re-endothelialization of injured carotid artery was impaired in zyxin-deficient mice, whereas the rate of cell proliferation was comparable to wild-type controls. Furthermore, endothelium-specific deletion of zyxin led to similar phenotypes. Knockdown of zyxin by shRNAs in primary human ECs significantly reduced cell migration in the wound-healing assay. Notably, forskolin enhanced endothelial migration in a dose-dependent manner, and this was dependent on zyxin through its interaction with vasodilator-stimulated phosphoprotein. In addition, forskolin promoted re-endothelialization of the injured carotid artery, and this was compromised by zyxin deficiency. Conclusion and Implications: This study reveals zyxin as a new player in endothelial repair, which is promoted by forskolin, after vascular injury. Thus, zyxin-mediated signaling might be a potential treatment target for diseases involving vascular injury.